INTERAKSI SOSIAL ANAK SPEECH DELAY DI SEKOLAH RAUDHATUL ATHFAL AL BARKAH KECAMATAN CITERAS KABUPATEN SERANG - Amat Hidayat (Jurnal Anak Bangsa, 2022)
The purpose of this study is to discuss about a child who experiences speech delay or speech delay disorders including aspects of language. This research uses descriptive qualitative research with case study techniques. Data acquisition in this research uses interview and observation techniques. The analysis focused on the causative factors, and the treatment of Speech Delay children aged 6 years. Based on the analysis, it was found that the disorder experienced by speech delay children is more of an expressive language disorder, which is caused by a lack of stimulus from parents, a bilingual environment. Alternative handling from the teacher is to invite parents to give more stimulus to children and the teacher always invites children to tell stories by talking, as well as confirming the words spoken by children when they are mispronounced by pronouncing the spelling correctly and slowly and repeated so that children can easily slowly follow it and get used to it